Gender Difference in Diabetes - Tonolo, Giancarlo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Sex and gender can affect the incidence, prevalence, symptoms, course and response to drug therapy in many illnesses, with sex (the biological side) and gender (the social‒cultural one) being variously interconnected. During the two days of the meeting "Gender Differences in Diabetic Disease" held in Olbia, Italy, on 4 and 5 December 2020, we discussed the various medical, social, ethnic, psychological and anthropological aspects of gender differences to build as broad a picture as possible of how these differences are present and evident in diabetic disease. Type 2 diabetes is the perfect example to justify gender medicine. During the meeting, we also tried to identify the still-unclear points that deserve further studies. This book describes several aspects of gender medicine that are related to diabetes. Physiopathology, drug treatment, sexual and psychological aspects, diabetes complication, migration, burden of working with a chronic disease and aspects related to COVID-19 infection are explored in a gender differentiation way. The authors are from different fields: medical doctors, biologist, psychologist, nurse, pharmacist, anthropologist and so on.